2021
DOI: 10.3389/fmed.2021.735276
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing and Doctor-Patient Communication During Consultations for Respiratory Tract Infections: A Video Observation Study in Out-of-Hours Primary Care

Abstract: Objective: Communication skills can reduce inappropriate antibiotic prescribing, which could help to tackle antibiotic resistance. General practitioners often overestimate patient expectations for an antibiotic. In this study, we describe how general practitioners and patients with respiratory tract infections (RTI) communicate about their problem, including the reason for encounter and ideas, concerns, and expectations (ICE), and how this relates to (non-)antibiotic prescribing in out-of-hours (OOH) primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Similarly, the Chinese government can indicate whether the drug is an antibiotic on drug packaging, and antibiotic identification campaigns included in the daily activities of guidance for rational drug use in schools and communities through a variety of media forms were recommended. In addition, barriers in doctor-patient communication often lead to a stronger willingness for doctors to use antibiotics in patients [ 36 ]. Patients and their caregivers often challenge doctors’ authority by rejecting treatment recommendations and such pressure may increase physician prescribing behavior [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Chinese government can indicate whether the drug is an antibiotic on drug packaging, and antibiotic identification campaigns included in the daily activities of guidance for rational drug use in schools and communities through a variety of media forms were recommended. In addition, barriers in doctor-patient communication often lead to a stronger willingness for doctors to use antibiotics in patients [ 36 ]. Patients and their caregivers often challenge doctors’ authority by rejecting treatment recommendations and such pressure may increase physician prescribing behavior [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach led to higher patient satisfaction, reducing late arising concerns, and improving understanding, time management, treatment adherence, and health outcomes. Findings showed that general practitioners who made room for the story of patients by using active listening techniques received more information about the ideas, concerns, and expectations (ICEs) and were able to successfully reassure patients that there was no reason to give antibiotics [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“… 55 A recent development in the area of non-participant observation includes an increasing use of video recordings. 19 , 33 , 34 This can be a useful data collection approach in primary care research particularly when studying patient–clinician communication practices related to AMS. 34 , 35 , 56 …”
Section: Designing and Conducting Qualitative Research In Ams: Import...mentioning
confidence: 99%
“… 19 , 33 , 34 This can be a useful data collection approach in primary care research particularly when studying patient–clinician communication practices related to AMS. 34 , 35 , 56 …”
Section: Designing and Conducting Qualitative Research In Ams: Import...mentioning
confidence: 99%